Influence of 6,7-dimethoxycoumarin on toxicity and pharmacodynamics of cyclophosphamide - WAN Yao-de; ZHENG Zhen-yuan; HUANG Jia-zheng; ZANG Qi-zhong; XU Jia-hong (Acta Pharmacologica Sinica, 2016)
When 40 mg/kg of 6,7-dimethoxycoumarin (DMOC) was given (ip) 15 min before sc cyclophosphamide (Cy), the LD50/7 d of Cy would be raised from 166 +/- 9 (100-245) to 294 +/- 4 (250-346) mg/kg (dose reduction factor 1.78) in Wistar rat. The 7 d survival rate of mice intoxicated by Cy was raised to 26.7%. To give 100 mg/(kg.d) of DMOC for 5 or 24 days, it prevented the chronic toxicity of Cy prolonged the life-span, elevated the 30 d survival rate of rats intoxicated by Cy to 45.3 and 42.5%, respectively. DMOC increased the WBC, weight of thymus and body of rats and mice intoxicated by Cy; raised colony-forming unit and reduced high plasma corticosterone of mice intoxicated by Cy. It also increased the RNA and DNA of bone marrow, liver and spleen. DMOC in combination with Cy did not reduce the antitumor effect of Cy.